PENGEMBANGAN KURIKULUM BERBASIS SENI TRADISIONAL MELALUI EKSTRAKULIKULER KARAWITAN - Irsyad Aldi Setyoaji; Yustina Fourta Amanda; Galih Hanantya Ramanda Putra; Syahrul Syah Sinaga (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to design and describe the implementation of an extracurricular curriculum based on the traditional art of Karawitan as an instrument for character education amidst the disruptions of the modern era. Facing the challenges of foreign cultural hegemony and individualistic lifestyles caused by globalization, Karawitan offers philosophical values such as mutual cooperation, tolerance, and communal harmony. Using a descriptive approach with a focus on implementation studies, this research highlights the pedagogical shift from theoretical learning based on rote memorization of notation (titilaras) to a Deep Learning approach that emphasizes kinesthetic experience, auditory sensitivity, and inner connection (rasa). The implementation results show that a modified curriculum integrating visual demonstration methods, movement imitation, and peer tutoring effectively increases student enthusiasm, reduces boredom, and bridges the disparity in motor and musical skills within the classroom. Furthermore, the gamelan ensemble has proven to transform into a sociocultural laboratory that organically internalizes the values of the Pancasila Student Profile. In conclusion, a structured, adaptive, and collaborative Karawitan extracurricular curriculum not only serves to preserve the cultural heritage of the archipelago but also provides a strategic foundation in cultivating young generations who possess mental resilience, noble character, and a strong local identity.